The Role of Digital Learning Ä±n Contemporary Education - Samarguliani, Nina (European Scientific Journal, ESJ, 2017)
The objective of this paper is to briefly discuss the role of digital learning in contemporary education. In this paper I am going to describe the types of digital learning and overview its main components as well as the ways of integrating it with traditional academic methods. I am going to list some main advantages and disadvantages of digital learning and try to find the best solutions in the process of integrating digital technologies in academic learning.